Paeonol Interferes With Quorum-Sensing in Pseudomonas aeruginosa and Modulates Inflammatory Responses In Vitro and In Vivo - Tang, Huaqiao; Yang, Dan; Zhu, Ling; Shi, Fei; Ye, Gang; Guo, Hongrui; Deng, Huidan; Zhao, Ling; Xu, Zhiwen; Li, Yinglun (Frontiers in Immunology, 2022)
Developing quorum-sensing (QS) based anti-infection drugs is one of the most powerful strategies to combat multidrug-resistant bacteria. Paeonol has been proven to attenuate the QS-controlled virulence factors of P. aeruginosa by down-regulating the transcription of QS signal molecules. This research aimed to assess the anti-virulence activity and mechanism of paeonol against P. aeruginosa infection in vitro and in vivo. In this study, paeonol was found to reduce the adhesion and invasion of P.aeruginosa to macrophages and resist the cytotoxicity induced by P.aeruginosa. Paeonol reduced the expression of virulence factors of P.aeruginosa by inhibiting QS, thereby reducing the LDH release and damage of P.aeruginosa-infected macrophages. Paeonol can inhibit bacterial virulence and enhance the ability of macrophages to clear P.aeruginosa. In addition, paeonol exerts anti-inflammatory activity by reducing the expression of inflammatory cytokines and increasing the production of anti-inflammatory cytokines. Paeonol treatment significantly inhibited the activation of TLR4/MyD88/NF-κB signaling pathway and decreased the inflammation response of P. aeruginosa-infected macrophages. Paeonol also significantly reduced the ability of P.aeruginosa to infect mice and reduced the inflammatory response. These data suggest that paeonol can inhibit the virulence of P.aeruginosa and decrease the inflammation response in P.aeruginosa-infected macrophages and mice, which can decrease the damage induced by P.aeruginosa infection and enhance the ability of macrophages to clear bacteria. This study supports the further development of new potential anti-infective drugs based on inhibition of QS and virulence factors.